Myoblastoma of the breast: Our experience and review of literature. (2016) - Sanguinetti, A.; Polistena, A.; Lucchini, R.; Monacelli, M.; Galasse, S.; Avenia, S.; Bugiantella, W.; Triola, R.; Cirocchi, R.; Rondelli, F.; Avenia, N.
Highlights: The myoblastoma or granular cell tumor is neoplasm that rarely affects the breast. Is very difficult to distinguish it from malignant neoplasms of the breast. The differential diagnosis is possible only with immunohistochemistry. A correct diagnosis avoids unnecessary surgeries. Abstract: Introduction: Breast myoblastoma or granular cell tumor involving the breast parenchyma has been described in detail for the first time since Abrikossoff in 1931. The location of this injury to the breast is very rare, accounting for between 5% and 15% of all cases of cancer of the granular cells. We present our experience regarding the identification of two cases because of the relative rarity of this tumor. It is often confused with breast cancer on clinical and radiological, and its diagnosis can then be difficult for physicians, radiologists and pathologists. Presentation of cases: We report the cases of two young women who came to our attention because of the presence of mass shoveled breast, mobile and accompanied by pain cycle independent. In both cases, mammography and ultrasound revealed the presence of heterogeneous mass and irregular, but in one of two such mass located at the Union of external quadrants of the left breast and was in contact with his serratus anterior and suspicion for malignancy. In both cases the 'histology combined with immunohistochemical study proved to be a granular cell tumor. Conclusion: Although a granular cell tumor of the breast is a rare tumor breast, should be considered in the differential diagnosis of benign and malignant lesions. Surgeons and pathologists should keep in mind when considering a granular cell tumor cells with abundant granular cytoplasm containing materials to avoid misdiagnosing breast cancer, which could lead to unnecessary surgery.